An Exploratory Study of the Use of Improvisation Games in Enhancing - Pretorius, Elinza (My University, 2016)
Prompted by troubling statistics of student throughput and dropout rates in South Africa, the problem of engagement is a key focus in this study. Three types of student engagement were attempted by exposing students to improvisation games in a tertiary environment. The research was conducted within a post-positivistic paradigm using survey questionnaires to determine the level of stimulation and engagement that improvisation offered respondents (Killen, 2010). The data was analysed according to categories that disclosed perceptions and definitions, and gauged levels of behavioural, emotional and cognitive engagement (Mahatmya, et al, 2012; Halverson et al, 2013; Fredericks et al, 2014). The results of the research found that students experienced improved levels of engagement, teamwork and enjoyment of the learning environment when exposed to improvisation games.
Keywords: Dropout rates; Student engagement; Higher education; Gaming